Pengaruh Komposisi Campuran Antosianin-Klorofil sebagai Fotosensitizer terhadap Efisiensi Dye Sensitized Solar Cell: Maya Dwi Fistiani, Fahru Nurosyid, Risa Suryana - Maya Dwi Fistiani Maya Dwi Fistiani; Fahru Nurosyid Fahru Nurosyid; Risa Suryana Risa Suryana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
This article is about fabrication of Dye Sensitized Solar Cell (DSSC) using mixture of anthocyanin and chlorophyllas fotosensitizer. Mixing dye aims to widen the absorbance area of natural dye.Anthocyanin is extracted from red cabbage andchlorophyll from spinach leaves with maseration methode. Mixture composition of dye anthocyanin:chlorophyll varying at 1:3, 1:1, and 3:1. Composition variation is performed to determine the effect of absorbance change on the efficiency of DSSC. Optic characterization using UV-Vis spectrophotometer and electric characterization using I-V meter. The characterization result showed that rasio 1:3 hasthe highest absorbance at wavelength 400 nm to 450 nm with highest efficiency 0,15%.